Oral shedding of herpes simplex virus type 2. Issue 4 (4th August 2004) - Wald, A; Ericsson, M; Krantz, E; Selke, S; Corey, L
Abstract : Objectives: Herpes simplex virus (HSV) 1 and HSV-2 reactivate preferentially in the oral and genital area, respectively. We aimed to define frequency and characteristics associated with oral shedding of HSV-2. Methods: Demographic, clinical and laboratory data of patients with documented HSV-2 infection and at least one oral viral culture obtained were selected from the University of Washington Virology Research Clinic database. Results: Of 1388 people meeting the entry criteria, 44 (3.2%) had HSV-2 isolated at least once from their mouths. In comparison with the 1344 people who did not have HSV-2 isolated from their mouth, participants with oral HSV-2 were more likely to be male (OR = 1.9, 95% CI 1.0 to 3.7), HIV positive (OR = 2.9, 95% CI 1.4 to 6.0), and homosexual (OR = 2.2, 95% CI 1.1 to 4.2), and to have collected a larger number of oral specimens (median 32 v 4, p<0.001). Of the 58 days with oral HSV-2 isolation, 15 (25%) occurred during newly acquired HSV-2 infection, 12 (21%) during a recurrence with genital lesions, three (5%) during a recurrence with oral lesions, and three (5%) during a recurrence with oral and genital lesions; 25 (43%) occurred during asymptomatic shedding. Oral HSV-2 was found less frequently than oral HSV-1 (0.06% v 1%, p<0.001) in people with HSV-1 and HSV-2 antibody, and less frequently than genital HSV-2 (0.09% v 7%, p<0.001). Conclusions: Oral reactivation of HSV-2 as defined by viral isolation is uncommon and usually occurs in the setting of first episode of genital HSV-2 or during genital recurrence of HSV-2.